1996
DOI: 10.1063/1.869003
|View full text |Cite
|
Sign up to set email alerts
|

An O(N) algorithm for Stokes and Laplace interactions of particles

Abstract: A method for computing Laplace and Stokes interactions among N spherical particles arbitrarily placed in a unit cell of a periodic array is described. The method is based on an algorithm by Greengard and Rokhlin [J. Comput. Phys. 73, 325 (1987)] for rapidly summing the Laplace interactions among particles by organizing the particles into a number of different groups of varying sizes. The far-field induced by each group of particles is expressed by a multipole expansion technique into an equivalent field with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 29 publications
0
80
0
Order By: Relevance
“…This will allow an easy integration into an O͑N͒ algorithm described earlier by Sangani and Mo. 5 The method is applied to a number of problems including chains of particles, drops, and porous particles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will allow an easy integration into an O͑N͒ algorithm described earlier by Sangani and Mo. 5 The method is applied to a number of problems including chains of particles, drops, and porous particles.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is intended to give expressions that are necessary so that the method of Sangani and Mo 5 can be extended to account for the presence of a rigid plane wall, a nondeformable gas-liquid interface, or both. The method is based on determining an image system for Lamb's multipoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lubrication effects require even greater values of N s , and hence multipoles, to determine hydrodynamic transport properties accurately. Since including the lubrication effects explicitly according to the scheme outlined by Sangani and Mo 5 slows down the convergence rate of the iterative method used in the algorithm, and since modifying the method for monodisperse suspensions outlined in Sangani and Mo 5 to account for the lubrication effects in bidisperse suspensions requires considerably more effort, it was chosen to carry out calculations with greater N s for one configuration and apply the correction obtained from the single configuration to the results obtained by N s ϭ3.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation results are obtained by modifying the method described in Sangani and Mo. 5 It is shown that modified effective-medium theories yield reasonably accurate estimates of the hydrodynamic transport coefficients and the conditionally averaged velocities.…”
Section: Introductionmentioning
confidence: 99%